2020
DOI: 10.1016/j.pharmthera.2020.107587
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L-selective inhibitors: A potentially promising treatment for COVID-19 patients

Abstract: The widespread coronavirus SARS-CoV-2 has already infected over 4 million people worldwide, with a death toll over 280,000. Current treatment of COVID-19 patients relies mainly on antiviral drugs lopinavir/ritonavir, arbidol, and remdesivir, the anti-malarial drugs hydroxychloroquine and chloroquine, and traditional Chinese medicine. There are over 2,118 on-going clinical trials underway, but to date none of these drugs have consistently proven effective. Cathepsin L (CatL) is an endosomal cysteine protease. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
278
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(292 citation statements)
references
References 103 publications
1
278
0
1
Order By: Relevance
“…Similarly, Ou and colleagues 3 show that cathepsin L inhibitor SID26681509 dramatically decreased SARS-CoV-2-S pseudovirions entry into 293/hACE2 cells, suggesting that cathepsin L is essential for priming of SARS-CoV-2 S protein in the lysosome. Indeed, this potential association has been recently proposed by Liu T et al 1 We have previously shown that the rst generation HIV protease inhibitor, saquinavir, blocks the activity of mouse cathepsin L (cathepsin V in humans) in macrophages. 4 Herein, we evaluated a possible inhibitory effect of several FDA-approved HIV protease inhibitors on the activity of cathepsin L.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Similarly, Ou and colleagues 3 show that cathepsin L inhibitor SID26681509 dramatically decreased SARS-CoV-2-S pseudovirions entry into 293/hACE2 cells, suggesting that cathepsin L is essential for priming of SARS-CoV-2 S protein in the lysosome. Indeed, this potential association has been recently proposed by Liu T et al 1 We have previously shown that the rst generation HIV protease inhibitor, saquinavir, blocks the activity of mouse cathepsin L (cathepsin V in humans) in macrophages. 4 Herein, we evaluated a possible inhibitory effect of several FDA-approved HIV protease inhibitors on the activity of cathepsin L.…”
Section: Introductionmentioning
confidence: 67%
“…The 2019 coronavirus disease pandemic (COVID-19) has mobilized efforts worldwide, and several ongoing clinical trials aimed at developing a vaccine or drug-based treatment for its control. 1 In a seminal paper, Hoffmann and colleagues demonstrated that SARS-CoV-2 employs the host cell surface receptor angiotensin-converting enzyme 2 (ACE2) for cell entry, and surface transmembrane serine protease 2 (TMPRSS2) for viral spike (S) glycoprotein priming. 2 These authors also reported that clinically proven serine protease inhibitor camostat, which is active against TMPRSS2, partially blocked SARS-2-S-driven entry into cells.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, SARS-CoV-2 infection has resulted in more than 80,000 laboratory-con rmed cases in China, with an overall mortality of appropriately 5% [13]. Unfortunately, despite many clinical drug trials underway, such as those for remdesivir, choloroquine, or lopinavir/ritonavir, no effective licensed drugs speci cally targeting SARS-CoV-2 are currently available [14][15][16]. The genomic sequence of SARS-CoV-2, published in 2020, shares 82% similarity with that of SARS-CoV [4,17] .…”
Section: Discussionmentioning
confidence: 99%
“…PT150 has unique, possibly additive effects as a direct anti-viral and as a potential modulator of the immune system. For these reasons, PT150 merits further study as a treatment for non-severe COVID-19and as a prophylactic for viral infection, alone and in combination with other potential antiviral agents, such as cathepsin-L-inhibitors, as recently suggested by Liu et al(36).…”
mentioning
confidence: 99%